Hormonal Imbalance of Estrogen and Progesterone, Its Association with PCOS, and Its Impact on Pregnancy Rates in Women from Thi-Qar Governorate - Challab, Mohammed (University of Thi-Qar Journal of Science, 2025)
Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder-affecting women of reproductive age, characterized by hormonal imbalances, irregular ovulation, and metabolic disturbances. The variability in estrogen and progesterone levels plays a crucial role in reproductive health. The aim of this study is to evaluate the levels of Estradiol-E2, progesterone (P4), and their effect on pregnancy rates in women with PCOS. It also covers the effect of follicle-stimulating hormone (FSH), luteinizing hormone (LH), testosterone, thyroid-stimulating hormone (TSH) and anti-Müllerian hormone (AMH). Additionally, metabolic markers such as fasting glucose, fasting insulin, body mass index (BMI), and insulin resistance (HOMA-IR). This study was conducted on 120 women aged 18-45 years, categorized into two age groups (18-30 and 31-45 years) to ensure balanced representation (60 with PCOS and 60 healthy controls). Serum hormone levels were measured using ELFA techniques, and metabolic parameters were evaluated using standard biochemical assays. PCOS patients exhibited significantly higher levels of (E2), LH, AMH, and testosterone, while progesterone and FSH were significantly lower compared to the control group (P < 0.05). HOMA-IR levels were significantly higher in PCOS patients, indicating an increased prevalence of insulin resistance. Pearson correlation analysis revealed a strong positive correlation between HOMA-IR and Estradiol-E2 (r = 0.558, ** P < 0.05) and a strong negative correlation with progesterone (r = -0.654, ** P < 0.05). The hormonal and metabolic dysregulations in PCOS negatively affect pregnancy rates, with Estradiol-E2, progesterone, and insulin resistance playing key roles.